Longitudinal assessment of lower-limb speed-strength qualities in elite U17 footballers using dual force-plate jump testing (VALD ForceDecks) - Ivanov, Danail (Universitas Tanjungpura, 2026)
Background Lower-limb speed-strength qualities are central to performance and injury prevention in youth football, yet their objective, longitudinal monitoring in elite U17 players remains uncommon in Eastern European academies. Objectives This study aimed to assess the level and longitudinal dynamics of lower-limb speed-strength qualities in elite U17 footballers across a general preparatory period. Methods Twenty-one players from the U17 academy of PFC Septemvri Sofia performed standardized Squat Jump (SJ), Countermovement Jump (CMJ) and Drop Jump (DJ, 30 cm) tests on a dual force-plate system (VALD ForceDecks FD4000, 1000 Hz) at the start (January 2026) and end (April 2026) of the period, spanning roughly 12 weeks; nineteen players formed the paired sample. Outcomes were analysed with descriptive statistics, percentage change, Cohen’s d and the Smallest Worthwhile Change (SWC). Results Practically meaningful improvements were observed in jump height for SJ (+10.1%, d = 0.90, large effect) and CMJ (+6.7%, d = 0.80, large effect), both far exceeding the SWC. The greater gain in SJ than CMJ and a negative augmentation index in April (CMJ – SJ < 0) indicated that the preparatory block emphasised concentric power while stretch-shortening-cycle (SSC) efficiency lagged. Baseline DJ revealed moderate reactive ability (RSI = 1.18 ± 0.21 m/s) with wide individual variability, and 63% of players exceeded a 10% concentric-impulse asymmetry at SJ, flagging an injury-prevention priority. Conclusion Periodized lower-limb strength work produced measurable concentric-power gains in U17 footballers, while identifying SSC efficiency, reactive strength and asymmetry correction as targets for the subsequent cycle. The study contributes a practical, data-driven monitoring framework for youth-football conditioning